A Correlational Study of Well-Being Psychology and Self Regulated Learning in Hafiz Student’s Learning Achievement in MA Tahfidzul Qur’an Isy Karima Karanganyar - Ahmad Zaky Romadlony; Mahsun Jayadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
This study aimed to find out correlation between well-being psychology and self-regulated learning on student learning achievement of hafiz in MA Tahfidzul Qur'an Isy Karima Karanganyar